Silver‐Catalyzed Dearomative [2π+2σ] Cycloadditions of Indoles with Bicyclobutanes: Access to Indoline Fused Bicyclo[2.1.1]hexanes - Tang, Lei; Xiao, Yuanjiu; Wu, Feng; Zhou, Jin‐Lan; Xu, Tong‐Tong; Feng, Jian‐Jun (Angewandte Chemie International Edition, 2023)
Bicyclo[2.1.1]hexanes (BCHs) are becoming ever more important in drug design and development as bridged scaffolds that provide underexplored chemical space, but are difficult to access. Here a silver‐catalyzed dearomative [2π+2σ] cycloaddition strategy for the synthesis of indoline fused BCHs from N‐unprotected indoles and bicyclobutane precursors is described. The strain‐release dearomative cycloaddition operates under mild conditions, tolerating a wide range of functional groups. It is capable of forming BCHs with up to four contiguous quaternary carbon centers, achieving yields of up to 99 %. In addition, a scale‐up experiment and the synthetic transformations of the cycloadducts further highlighted the synthetic utility. A silver Lewis acid catalyzes dearomative [2π+2σ] cycloadditions of N‐unprotected indoles and bicyclobutanes to afford indoline fused bicyclo[2.1.1]hexanes (BCHs) bearing up to four contiguous quaternary carbon centers in high yields and with an opposite regioselectivity compared to the classical pathway.